Pengembangan LKPD Berkarakter Berbasis Quantum Teaching dan Implikasinya dalam Pembelajaran Biologi Kelas VII SMP : Development of LKPD with Character Based on Quantum Teaching and Its Implications in Biology Learning for Class VII SMP - Ica Wandari Anisia; Asni Johari; Bambang Hariyadi (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2022)
The character of students, in general, is still not well developed. We need teaching material for LKPD (Student Worksheet) enriched with character values. This study aims to produce character-based LKPD adopted from quantum teaching and determine teachers' and students' feasibility and responses to the LKPD. This study uses the ADDIE development model, which consists of five stages. LKPD was validated by the material validator three times with a final score of 56 and a response value of 87.5% (excellent category), while the media validator twice with a final score of 64 and a response value of 100% (excellent category). Furthermore, two teachers carried out practitioner validation with an average score of 80.5 and a response value of 87.5% (the product is feasible to be tested and applied in learning). One-on-one trials with three students as the subject got a score of 166 and a response value of 86.5% (excellent category). The small group trial with nine subjects scored 289, and the response value was 89.2% (excellent category). The study concludes that the LKPD based on quantum teaching can be used in class VII SMP learning.